Primeiro registro de ocorrência do bivalve exótico Corbicula fluminea (Muller, 1774) na microbacia do Rio Jundiaí-mirim, SP, Brasil - Beghelli, Frederico Guilherme de Souza [UNESP]; Pompêo, Marcelo Luiz Martins; Carlos, Viviane Moschini [UNESP] (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2014)
Corbicula fluminea is a naturally occurring Asian bivalve that was spread around the world, and which has become a highly aggressive invasive species in many countries. C. fluminea has many ecological, economic and social impacts, such as the extinction of native species, ecosystems alterations, and damage to pipes and hydropower turbines. As an illustration of the potential damage that proliferation of C. fluminea can cause, it is noted that the United States government spends more than 1 billion dollars per year to control this species. This work recorded the first occurrence of the Asian clam C. fluminea in the Jundiaí-Mirim Basin, SP, Brazil, and included basic ecological information such as density, frequency distribution of size and species distribution along the basin. Seventy-eight individuals were sampled with a van Veen grab along the basin. The specimens were identified and measured. The exotic species was found only in two of four sampling points and its distribution was possibly influenced by sediment composition and water flow. Moderate densities were calculated, ranging from 12 to 235 ind.m-2. Our data suggest that young populations are growing in the basin. The presence of C. fluminea is a concern for the maintenance of the ecosystem and for different water uses in the Jundiai region.
First occurrence of the exotic asian clam Corbicula Fluminea (Muller, 1774) in the Jundiaí-Mirim river basin, SP, Brazil
Keywords: Bivalve; Corbiculidae; Invasive species